MEMAHAMI IKLIM KOMUNIKASI ORGANISASI DALAM FORUM KELOMPOK USAHA BERSAMA (KUB) NELAYAN TAMBAK LOROK - Isabela Laras Anindyo; Turnomo Rahardjo; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Forum Kelompok Usaha Bersama (KUB) Nelayan Tambak Lorok as a fisherman organization formed by Dinas Kelautan Kota Semarang with the aim of improving the welfare of self-reliance. In fact, fishermen have another goal in organization which causes low productivity inside. The existence of an organizational communication climate affects organizational productivities. For this reason, this study aims to describe the organizational communication climate which formed in the Forum based on the dimensions of openness communication, supportiveness, participation in decision making and high work motivation of members. This study uses a qualitative research method with an ethnographic approach to communication that is supported by the concept of Organizational Communication Climate. The research subjects are the committee and members of the Forum Kelompok Usaha Bersama (KUB) Nelayan Tambak Lorok. Based on the data which obtained through observation and interview, the result shows that the communication behaviours of members in Forum indicate a closed communication which can be seen from verbal and non-verbal communication that appears such as distance, non-dramatizing attitudes, and unfriendly attitudes. The unsupportive attitude is also seen among members which is indicated by low concern for fellow members, indifferent attitude, and a low sense of belonging. Unsupportive behavior is motivated by the